Assessment of Microplastics in Road Dust and Their Human Health Impacts: A Review - Zaman Shakil, Md. Shakilur; M. G., Mostafa (Al-Nahrain Journal of Science, 2026)
Microplastics (MPs), which are resistant to degradation in the environment, have been identified in air, dust, soil, and water samples throughout the world. This review aims to represent the assessment of microplastics in road dust and their impacts on human health. The study considered available data from journals, books, and reports published within the last twenty years on MPs in road dust. Tire wear, textiles, waste disposal, road markings, building materials, and packaging material, these are the leading sources of microplastics in road dust. To identify the MPs in road dust, microscope, FT-IR, Raman spectroscopy, GC-MS, and SEM-EDX were used. The dominant polymers in road dust were PP, PE, PVC, and PET. This review found the MPs deposition rates varied from 22 to 3.43×106 MPs/m²/day, which significantly depends on population density and traffic intensity. However, the MPs abundance in road dust ranged from 0.068 to 20.16 particles/g. Consequently, an average of 1063 and 3223 microplastic particles are ingested per year by adults and children, respectively, which may cause numerous human health problems such as gastrointestinal disorders, immune system disruption, respiratory issues, cancer, etc. Hence, all types of plastics should be collected, and enhanced recycling could be a solution to control microplastic pollution from road dust.